Polycyclic aromatic hydrocarbons in US and Swedish smokeless tobacco products - McAdam, Kevin G (BioMed Central, 2013)
BACKGROUND: Debate about the health implications of using smokeless tobacco products (STPs) has prompted considerable interest in characterising their levels of toxic and carcinogenic components. In the present study seventy smokeless tobacco products from the US and Sweden, categorized as chewing tobacco, dry and moist snuff, hard and soft pellets, plug, and loose and portion snus, were analysed for twenty one polycyclic aromatic hydrocarbons (PAHs). The tested brands represented 80-90% of the 2008 market share for the major STP categories in these two countries. RESULTS: There were significant differences in the total and individual PAH concentrations in the different styles of product. Substantially higher levels of total PAHs (10–60 fold) were found in moist and dry snuff and soft pellets than in the other smokeless tobacco styles. The individual PAH concentrations followed the same patterns as total PAHs except for naphthalene, for which the highest concentrations were found in snus and moist snuff. Good correlations were obtained between benzo[a]pyrene (B[a]P) and all the other PAHs except naphthalene, 1-methylnaphthalene and 2-methylnaphthalene, providing evidence for the first time that it can be used as a good marker for PAHs in STPs. Results were generally in good agreement with two previous studies of PAHs in STPs, except for naphthalene for which significantly lower concentrations were found than previously reported. Analysis of the ratios of different PAHs confirmed that the use of fire-cured tobaccos in the snuffs and soft pellet were the major source of PAHs in these product styles, and provided, for the first time, some indications as to the source of PAHs in the other STP styles, including petrogenic and other combustion sources. CONCLUSIONS: This study confirms the presence of PAHs in STPs, and identifies substantial differences between the levels in different STP categories. Since previous studies of naphthalene concentrations in STPs differed so markedly from those found in this study, it is recommended that further work on PAH determination is undertaken to investigate the source of this discrepancy.